Modeling Integrated Waqf-Sukuk for Climate Action (SDG13) - Rusydiana, Aam Slamet; Sukmana, Raditya; Laila, Nisful; Bayram, Kamola (SMART Insight, 2023)
The discussion on tackling climate change is summarized in the thirteenth SDGs goal. On the other hand, waqf is an instrument of Islamic social funds that has a sustainable nature and has the relevance of waqf to the SDGs, so it has the potential to be developed in its role in fighting climate change and its impacts. This study seeks to see the waqf model that is relevant to the goals of the SDGs by determining the priority of the waqf model that can be applied in Indonesia which is in line with the objectives of SDGs 13 using ANP method. The results of the study indicate that the Waqf & Sukuk model is the right model to support the achievement of the thirteenth goal of the SDGs, namely climate change management. This study also proposes a WOFI (Waqf Owned Financial Intermediary) model framework that is suitable for this purpose.